Study of Coordination on Protection Relay in High Voltage Transmission 150 kV (Payakumbuh – Koto Padang, West Sumatra) - Zulkarnaini Zulkarnaini; Rizki Muhammad (MATEC Web of Conferences, 2018)
The disturbance of the high voltage transmission can be caused by a short circuit, overload, lightning surge, and other natural disturbances. That disturbance can lead to disruption of the distribution of electricity and damage to the electric power system installation equipment. A reliable protection system that can identify the disturbance quickly and also can securing affected parts of the system from other parts that can still operate normally are needed. Protection system operation may fail due to various factors; therefore, in addition to primary protection required backup protection that can work as primary protection fails to work. Distance relays can be used as primary protection as well as remote backup protection on high-voltage transmission. While overcurrent relay (OCR) and ground fault relay (GFR) is used as a local backup if distance relay failed to work. This research conducted a study of protection relays coordination for primary protection or backup protection on the high-voltage transmission that connects to Payakumbuh substation and Koto Panjang substation. Coordination is done by calculating the distance relay settings that use as primary protection as well as remote backup protection relay settings and calculating the overcurrent and ground fault relay that used as local backup protection. From the calculation, we get setting time to coordinate distance relay, overcurrent relay, and ground fault relay. Setting time was conducted to the first zone of the distance relay within 0 sec, and the second zone within 0.4 sec and third zone within 1.2 sec. For overcurrent relay and ground fault relay use time delay 1 second where the value is above the value that used in the second zone of distance relay. Distance relay can be coordinated with the auto-reclose relay to close the circuit breaker automatically sometime after a temporary disturbance. Setting that use to auto reclose relay is dead time 1 second and reclaim time 40 second. The coordination between the distance relay with auto-reclose relay can improve the quality of distribution of electrical energy.